A Corrective Justice Account of Disgorgement for Breach of Contract by Analogy to Fiduciary Remedies. Issue 1 (2nd February 2016) - Sangiuliano, Anthony Robert
Abstract : A corrective justice account of a private law remedy attempts to the explain the remedy as giving back to the plaintiff something to which the plaintiff had a prior right that was breached by the defendant's receipt of that thing. It has proven challenging to explain how disgorgement for breach of contract is consistent with corrective justice. This remedy gives to the plaintiff any profit that a defendant received from a third party by breaching a contract with the plaintiff. In this paper, I critique two leading attempts to show how disgorgement for breach of contract is consistent with corrective justice. I argue that these attempts fail, and I suggest that a plausible corrective justice account of disgorgement should be based on something other than the nature of the contractual rights borne by a plaintiff. I then develop an alternative account based on an analogy between disgorgement for breach of contract and disgorgement for breach of fiduciary duty. To do so, I draw on recent scholarship on the consistency of disgorgement for breach of fiduciary with corrective justice and analyze the leading judicial decision on disgorgement for breach of contract by the UK House of Lords in Attorney General v. Blake . I argue that the fiduciary-based account can provide a plausible explanation for how disgorgement effectuates corrective justice by giving back to a plaintiff something to which he had an antecedent right that the defendant violated by profiting from a breach of contract.